Assessment Of Select Words In English That Are Difficult To Pronounce: Strategic Ways Teachers Can Help Pupils To Overcome The Struggles: A Case Study Of Public Primary Schools In Akwa Ibom State - EKAEBA, OKON; ENYENE, DINAH JULIUS (Afrischolar Discovery Repository (Annex), 2024)
This study assessed select words in English that are difficult to pronounce and the strategic ways teachers can help pupils to overcome the struggles. In carrying out the study, descriptive survey design was adopted for this study. The study was carried out in Akwa Ibom State. The targeted population for the study comprised all pupils in public primary schools in Akwa Ibom State. Stratified random sampling technique was used to select 60 pupils from each of the three senatorial districts which gave a total of 180 respondents used for the study. The instrument used for data collection was a structured questionnaire titled “Difficult Words for Pronunciation in English Questionnaire (DWPEQ)”. Face and content validation of the instrument was carried out by an expert in test, measurement, and evaluation in order to ensure that the instrument has the accuracy, appropriateness, and completeness for the study under consideration. The reliability coefficient obtained was 0.81, and this was high enough to justify the use of the instrument. The researcher subjected the data generated for this study to appropriate statistical technique such percentage analysis to answer research questions. The findings of the study revealed that among others, words with silent letters are the most difficult words for pupils to pronounce and also that “explicit phonetic instruction” among other strategic methods teachers can employ to help pupil’s overcome pronunciation difficulties was the most efficient. The study concluded that pronunciation is critical in language acquisition, affecting communication and proficiency, and that English presents unique challenges to non-native speakers due to its complex phonetic structures andirregular spellings. One of the recommendations was that teachers should ensure that there is a structured approach to pronunciation practice integrated into the daily classroom routine.